Innovation and safety in critical care: should we collaborate with the industry? Yes - Gordon,AC; Russell,JA (Intensive Care Medicine, 2018)
As clinicians we all want to improve care for our patients. We can do that in two ways. We can do what we currently do better, or we can do new things (better). The development of large clinical academic trials groups and networks has enabled clinicians to understand what particular clinical care leads to better patient-centred outcomes. Ironically, we have learnt that many of our “usual” interventions either provided no benefit or were even harmful. Thus, clinicians, can improve the safety and effectiveness of critical care practice. But when it comes to innovation - new therapeutics and novel diagnostics - then it is hard to imagine that we could achieve this without input from or partnership with industry. Furthermore, a brief walk around an ICU illustrates cogently the vast number of devices used and drugs being infused, all of which originated in industry, some with much and some with little clinician scientist input. We argue herein that such collaboration is not only acceptable, it is necessary and can be done ethically, using established guidelines and conflict of interest disclosure.